Testing guidelines for connection of solar photovoltaic farm to distribution grid: The Malaysian experience - Yong J.Y.; Ramachandaramurthy V.K.; Tan K.M.; Pouryekta A.; Ekanayake J.B.; Jayasinghe A.E. (John Wiley and Sons Ltd, 2023)
Electric inverters; Electric power system interconnection; Electric power transmission networks; Photovoltaic cells; Power quality; Renewable energy resources; Solar concentrators; Solar system; Comprehensive testing; Distribution grid; Grid interconnections; Photovoltaic systems; Renewable energy source; Solar photovoltaic plants; Solar photovoltaic technology; Solar photovoltaics; Solar power generation